2011
DOI: 10.1177/2156759x1101400306
|View full text |Cite
|
Sign up to set email alerts
|

Using Culturally Competent Responsive Services to Improve Student Achievement and Behavior

Abstract: This article illustrates standards blending, the integration of core academic and school counseling standards, as a culturally alert responsive services strategy to assist in closing the achievement gap while also enhancing employability skills and culturally salient career competencies. The responsive services intervention described in this article resulted in knowledge gains in both the school counseling and language arts curriculum competencies for a diverse group of 78 high school students. The article inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…In their review of school counseling outcome research, Whiston, Tai, Rahardja, and Eder () concluded that proactive curriculum interventions delivered by school counselors improved student outcomes. For example, classroom guidance enhanced academic development (Galassi & Akos, ) and improved the behavior of student participants (Schellenberg & Grothaus, ). This study evaluated the efficacy of a classroom guidance curriculum.…”
Section: Purpose Of the Studysupporting
confidence: 89%
See 1 more Smart Citation
“…In their review of school counseling outcome research, Whiston, Tai, Rahardja, and Eder () concluded that proactive curriculum interventions delivered by school counselors improved student outcomes. For example, classroom guidance enhanced academic development (Galassi & Akos, ) and improved the behavior of student participants (Schellenberg & Grothaus, ). This study evaluated the efficacy of a classroom guidance curriculum.…”
Section: Purpose Of the Studysupporting
confidence: 89%
“…The findings consistently showed that the demographic variables and pretest scores specified in the models did not explain a considerable amount of the variance in the posttest scores that was due to individual differences across students (ranging from 20% to 97%). The findings also supported previous research that highlighted the potential efficacy of classroom guidance efforts by school counselors (Galassi & Akos, ; Schellenberg & Grothaus, ; Whiston et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Contextually responsive PBL can address achievement gaps by valuing diversity (cultural, racial, ability level, etc.) as a source of knowledge contributing to personal and social development [36]. Emphasizing personal relevance can also improve information retention.…”
Section: Why To Learnmentioning
confidence: 99%
“…In today's increasingly diverse workforce, intercultural competency is a highly valued skill. In international schools, which can consist of more than 30 different nationalities, intercultural competency of teachers, administrators and the school organization structures can have a significant impact on student academic achievement (Callins, 2006;Oller, Vila, & Zufiaurre, 2012;Schellenberg & Grothaus, 2011;Sleeter, 2012;Snowball, 2009). Deardorff (2009) defines intercultural competency as a set of attitudes, skills and values that influence a person's behavior and communication to effectively achieve one's goals in a culturally diverse environment.…”
Section: Background and Need For The Studymentioning
confidence: 99%
“…Within K-12 schools, pedagogy that has been specifically designed for cultural diversity is called culturally responsive pedagogy (Callins, 2006;Schellenberg & Grothaus, 2011).…”
Section: Use Of Terms In Literaturementioning
confidence: 99%